Implementation of the Waterfall Method in Narotama Career Center Information System Development - Pamudji, Prasanti Oktaviana; Kamisutara, Made (STMIK Banjarbaru, 2024)
Narotama Career Center is a career center institution at Narotama University and is tasked with helping students prepare themselves through various types of training and as an information center regarding the world of work or entrepreneurship. However, the results of an interview with one of the student affairsstaff stated that in fact the information dissemination carried out was considered less effective because it was only carried out through social media. All activities are also hampered because there is no integrated system for collecting data on training and registering available job vacancies. This research was conducted to design and develop a website-based Narotama Career Center Information System using the SDLC Waterfall Model method. System design uses Unified Modeling Language from the results of previous needs analysis. System development was carried out using Laravel and Tailwind CSS and Figma. The trials that have been carried out obtained a score of 85 on the System Usability Scale which is in the Acceptable category, which shows that the system is very easy to use.Keywords: Career Center; Website; Waterfall; UML DiagramÂ AbstrakNarotama Career Center merupakan lembaga pusat karir yang ada di Universitas Narotama dan bertugas untuk membantu mahasiswa dalam mempersiapkan diri melalui berbagai macam pelatihan dan sebagai pusat informasi mengenai dunia kerja ataupun kewirausahaan. Namun dari hasil wawancara dengan salah satu staff kemahasiswaan menyebutkan bahwa faktanya penyebaran informasi yang dilakukan dinilai kurang efektif karena hanya dilakukan melalui sosial media. Seluruh kegiatan juga terhambat karena tidak adanya sistem yang terintegrasi untuk melakukan pendataan pelatihan dan pendaftar lowongan pekerjaan yang tersedia. Penelitian ini dilakukan untuk membuat rancangan dan melakukan pengembangan Sistem Informasi Narotama Career Center berbasis website dengan menggunakan metode SDLC Model Waterfall. Perancangan sistem menggunakan Unified Modelling Language dari hasil analisis kebutuhan sebelumnya. Pengembangan sistem dilakukan menggunakan Laravel dan Tailwind CSS serta Figma. Uji coba yang telah dilakukan memperoleh skor 85 dari System Usability Scale yang masuk ke kategori Acceptable yang menunjukkan bahwa sistem sangat mudah digunakan.Â